A new target: AlkBH2 promotes bladder cancer by upregulation of inflammation - Zhangjie Yang; Jinhu Ma; Ziyang Qiang; Wenhao Xie; Liang Jiao; Guojun Chen (PLoS ONE, 2026)
A close relationship exists between inflammation and cancer. Recent studies have highlighted inflammation as a significant contributor to the progression of bladder cancer. However, the role of alkyladenine DNA glycosylase homolog 2 (AlkBH2), an enzyme involved in DNA repair and a member of the AlkB family, in the context of bladder cancer inflammation remains largely unexplored. Our findings demonstrate that AlkBH2 promotes the proliferation, colony formation, migration, and invasion of bladder cancer cells. Mechanistically, AlkBH2 activates the nuclear factor-kappa B (NF-κB) signaling pathway, which in turn drives the progression of bladder cancer. These results suggest that AlkBH2 plays a critical oncogenic role in bladder cancer by modulating inflammation through the activation of the NF-κB pathway. These findings highlight the potential of AlkBH2 as a therapeutic target for bladder cancer treatment.